1988
DOI: 10.1002/hon.2900060307
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenotyping in Hodgkin's disease

Abstract: This review presents and discusses the immunogenotypic findings in 112 cases of Hodgkin's disease (HD) and eight Hodgkin's cell lines. Clonal rearrangements of the T cell receptor gamma and beta chain, as well as immunoglobulin heavy and light chain genes, are detected in the majority of nodular sclerosis and lymphocytic depletion subtypes. Together with the recent immunophenotypic data, these findings are in favour of the view that HD is a disease of activated lymphoid cells. Further investigations will be ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…If the same phenomenon occurs in H D , the occurrence of breakpoints at these sites may help to identify the lineage of the tumor, a subject of intense study in recent years. Since some evidence of both B-cell and T-cell lineage in H D has been found by both immunohistochemical (Stein et al, 1986;Coles et al, 1988;Cibull et al, 1989;Dallenbach and Stein, 1989) and molecular genetic methods (Griesser and Mak, 1988), the occurrence of translocations at the sites of antigen receptor genes would be expected in at least some cases. However, only band 14q32 has been reported to be involved with any frequency.…”
Section: Discussionmentioning
confidence: 99%
“…If the same phenomenon occurs in H D , the occurrence of breakpoints at these sites may help to identify the lineage of the tumor, a subject of intense study in recent years. Since some evidence of both B-cell and T-cell lineage in H D has been found by both immunohistochemical (Stein et al, 1986;Coles et al, 1988;Cibull et al, 1989;Dallenbach and Stein, 1989) and molecular genetic methods (Griesser and Mak, 1988), the occurrence of translocations at the sites of antigen receptor genes would be expected in at least some cases. However, only band 14q32 has been reported to be involved with any frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, the heterogeneous nature of Hodgkin's disease is the reason for the lack of accordance in data concerning the cellular origin of the neoplastic population on the one hand and the karyotype changes on the other. Several molecular genetic studies have demonstrated that H and SR cells show rearrangements and expression specific for either B-cell or for T-cell lineage (Falk et al 1987;Griesser et al 1986a, b;Griesser and Mak 1988;O'Connor et al 1987;Tesch et al 1988). Moreover, the results obtained on established cell lines and on primary Hodgkin's lymphomas suggest that H and SR cells are immature lymphoid cells that are activated by as yet unknown mechanisms (Falk et al 1987;Tesch et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Immune receptor gene analyses are of limited value in the differential diagnosis of Hodgkin's disease (HD) versus non-Hodgkin's lymphoma in morphologically equivocal cases. Immunogenotyping sometimes may not help in differential diagnosis between peripheral T cell lymphoma with atypical large T blasts and HD (usually of mixed-cellularity subtype or unclassified): TCRI3 rearrangements have been observed in HD as well [60,75,144]. The separation of HD from non-Hodgkin's lymphoma thus remains impossible at times.…”
Section: Tcr Gene Probesmentioning
confidence: 99%